THE USE OF CHEMICALLY ACTIVATED FIR CONE CARBON IN THE REMOVAL OF Pb²⁺ CONTAMINATED AQUEOUS SOLUTIONS - MÂNZATU, Carmen; MAJDIK, Cornelia; NAGY, Boldizsár (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Fir cone biomass was used as a precursor for the preparation of activated carbon by sulfuric acid treatment and activation. It is known that the activated carbon from different biomass sources has a wide range of applications in water treatment. Therefore, fir cone activated carbon (FCAC) was prepared from raw fir cone by chemical treatment and used in various experiments to test its functions for the removal of Pb2+. The influences of different parameters like contact time, initial lead concentration, initial pH, biomass quantity and temperature were studied. Adsorption isotherm and kinetic models were used to analyze the equilibrium data. It was found that the Freundlich isotherm model and pseudo-second-order model describe better the Pb2+ biosorption process. The changes in morphological structure after lead ions-biomass interactions were evaluated by SEM analysis. From these studies, it can be concluded that the fir cone activated carbon could be a promising and effectively employed bioadsorbent for the removal of Pb2+ ions from aqueous solutions.